Prediction of Ship Motions in Irregular Waves Based on Response Amplitude Operators Evaluated Experimentally in Noise Waves - Bielicki Sebastian (Polish Maritime Research, 2021)
The most common methods for predicting ship roll motions in a specified sea state are direct measurements of motions in a representative irregular wave realisation (time domain) or calculations of motions from response amplitude operators (RAOs) in the frequency domain. The result of the first method is valid only for the tested sea state, whilst the second method is more flexible but less accurate. RAO-based predictions are calculated assuming a linear model of ship motions in waves. RAO functions are usually evaluated by means of tests in regular waves for a limited number of frequencies and a constant wave amplitude. This approach is time-consuming and the discrete form of the RAO functions obtained for a limited number of frequencies may lead to discrepancies in the prediction of seakeeping and often does not allow the actual amplitude of the response in resonant frequency to be determined. Another challenge is the appropriate selection of wave amplitude for tests due to the considerable influence of viscous damping on roll response in irregular sea waves. There are alternative methods for the experimental determination of RAO functions and one of them is presented in this study. The presented approach allows RAO functions to be evaluated in one run by the generation of irregular waves characterised by a white or coloured noise spectrum. This method reduces the experiment duration, with almost continuous RAO characteristics obtained. The flat (white noise) and linear (coloured noise) wave spectral energy characteristics are considered in the experiment and the obtained predictions are compared with the results of accurate measurements in irregular waves.